CAROTID DISEASE IN DIABETIC PATIENTS UNDERGOING CORONARY ARTERY BYPASS GRAFTING - Shahid, Muhammad; Abid, Abdul Rehman; Dar, Muhammad Ashraf; Noeman, Ahmad; Amin, Shahid; Azhar, Muhammad (Journal of Ayub Medical College Abbottabad, 2011)
Objective: To compare the severity of carotid artery disease in diabetic and non-diabetic patients undergoing coronary artery bypass grafting. Methods: From January to June 2008, 379 patients undergoing elective coronary artery bypass surgery were preoperatively evaluated for the presence of carotid stenoses by duplex scanning. Patients were divided into two groups, Group I, 156 (41.2%) diabetic patients and Group II, 223 (58.8%) non-diabetic patients. Results: There were 314 (82.8%) males and 65 (17.2%) females with a mean age of 57.2±9.1 years. In diabetic group there were 125 (80.1%) males and 31 (19.9%) females with a mean age of 56.3±8.9 years. Left main stem stenosis was present in 59 (37.8%) diabetics and 45 (20.2%) non-diabetics (p<0.0001). Diffuse disease in left anterior descending (LAD) artery was observed in more diabetic patients 72 (46.2%) as compared to non-diabetics 83 (37.2%) (p<0.295). Single tight stenosis in LAD was observed in more non-diabetics. Significant carotid artery stenosis was observed in 50 (13.2%) patients. Carotid artery stenosis was observed in 30 (19.2%) diabetics as compared to 20 (9%) non-diabetics (p<0.004). Analysis of percentage stenosis of carotid artery disease in the study population revealed that >70% stenosis was present in 20 (5.3%) with 13 (8.3%) diabetics and 7 (3.1%) non-diabetics (p<0.025). Stenosis of 50- 70% was observed in 30 (7.9%) of which 17 (10.9%) were diabetics and 13 (5.8%) were non-diabetics. Conclusion: Presence of diabetes mellitus is associated with diffuse coronary artery disease and significant carotid artery disease in patients undergoing coronary artery bypass grafting. Keywords: Atherosclerosis, Coronary artery disease, Carotid artery disease, Coronary artery bypass grafting, Diabetes Mellitus